Rancangan Aplikasi Penjualan Tunai Komputer Pada Dony Komputer Purwokerto - Sri Heneng Prasastono; Mohammad Hidayatul Holili (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
The problem with Dony Computer is that sales transactions still use a manual system using ledgers for each recording, so that errors often occur which will cause losses for Dony Computer and inefficient reporting to shop owners. The aim of designing a sales information system is to make it easier for the administration to process existing data. Application tools that have been created with PHP and a MySQL database can provide a smooth process for inputting and storing data and reports provided to shop owners. By using a system development method, namely the System Development Life Cycle. The results of this research create a sales application design that can make it easier for stores to collect data on goods and sales data to make it better and more accurate. Apart from that, the level of effectiveness of this application is quite high as seen from customer satisfaction with a good and fast transaction process.